The "Problem" of Religion, Christianity, and the Capacity of Community. (1st October 2015) - ,
Abstract : Ananda Abeysekara's essay takes up Gil Anidjar's objection to the way Nancy ignores the problematic legacy of "religion" inseparable from Christianity. Abeysekara focuses on the politics of exclusion that Anidjar identifies in the Christian notions of "fraternity" and "community" supposedly connected to the problem of religion. Thus, for Anidjar, the definition of religion arises as a problematic that is compounded by the legacy of "fraternization, " needing critique. Abeysekara asks if a critique of fraternity and community can serve as a censure of the way in which the definition of religion has been taken over by "Christianity." For Abeysekara, counterposing the work of scholars such as Talal Asad and Jacques Derrida enables a reconsideration of the question of monastic brotherhood in relation to the Theravada Buddhist tradition, and what it means to claim that fraternity and community qua Christianity constitutes a problem of religion. Critiquing the problem of fraternity in this way misses exactly the authorized forms of religious practice guided by the cultivation of specific kinds of "capacity" like obedience.